The Attentive Life - "Ford, Leighton." ("Downers Grove, Ill. :")
Includes bibliographical references (p. [212]-222).
Keywords: GOD -- OMNIPRESENCE.;SPIRITUAL LIFE -- CHRISTIANITY.;PRAYER -- CHRISTIANITY